2011
DOI: 10.1016/j.ajpath.2011.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Contribute to IL-4 Production and Shape the T-Helper Cytokine Profile and Inflammatory Response in Pulmonary Cryptococcosis

Abstract: Susceptibility to infection with Cryptococcus neoformans is tightly determined by production of IL-4. In this study, we investigated the time course of IL-4 production and its innate cellular source in mice infected intranasally with C. neoformans. We show that pulmonary IL-4 production starts surprisingly late after 6 weeks of infection. Interestingly, in the lungs of infected mice, pulmonary T helper (Th) cells and eosinophils produce significant amounts of IL-4. In eosinophil-deficient ⌬dblGATA mice, IL-33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 82 publications
1
50
1
Order By: Relevance
“…Along with the widely published fact that eosinophilia has often been associated with ineffective immune responses against C. neoformans, it has been shown that eosinophils bind C. neoformans in the presence of opsonizing antibodies (41), that late-phase C. neoformans-induced pulmonary eosinophilia is IL-5 dependent (8), and that eosinophils have C. neoformans-derived antigen-presenting capabilities (42,43). Recently eosinophils were found to be important producers of IL-4 and thus are contributors to nonprotective Th2 responses (44). It has remained unclear whether IL-5 and eosinophils are mere bystanders during an otherwise pathogenic Th2 process or whether they were active contributors to C. neoformans disease.…”
Section: Il-5 Overexpression Reverses the Sp-dmentioning
confidence: 99%
“…Along with the widely published fact that eosinophilia has often been associated with ineffective immune responses against C. neoformans, it has been shown that eosinophils bind C. neoformans in the presence of opsonizing antibodies (41), that late-phase C. neoformans-induced pulmonary eosinophilia is IL-5 dependent (8), and that eosinophils have C. neoformans-derived antigen-presenting capabilities (42,43). Recently eosinophils were found to be important producers of IL-4 and thus are contributors to nonprotective Th2 responses (44). It has remained unclear whether IL-5 and eosinophils are mere bystanders during an otherwise pathogenic Th2 process or whether they were active contributors to C. neoformans disease.…”
Section: Il-5 Overexpression Reverses the Sp-dmentioning
confidence: 99%
“…IL-33 acts on a variety of cells of the innate arm of immunity, including neutrophils, macrophages, dendritic cells, mast cells, basophils, and eosinophils, and functions as an amplifier of inflammation (5)(6)(7)(8)(9)(10)(11)(12)(13). Recent studies have suggested that IL-33 plays a role in infection-related inflammation, as IL-33 is protective against infection by opportunistic pathogens such as Pseudomonas aeruginosa, Pneumocystis murina, Cryptococcus neoformans, and polymicrobes (6,8,9,14). Prior to this study, there had been no publications regarding the role of IL-33 in Candida albicans infections.…”
mentioning
confidence: 99%
“…Following intratracheal C. neoformans infection, genetically susceptible C57BL/6 mice were shown to have marked IL-5-dependent eosinophil recruitment that was associated with crystal deposition and airway epithelial damage (44). Eosinophils were also shown to produce IL-4, which promotes Th2 responses and contributes to immunopathology during pulmonary cryptococcal infection (40). Conversely, despite the ability to internalize and kill C. neoformans in vitro (59,60), there is relatively little evidence that neutrophils contribute to protective host defense.…”
Section: Discussionmentioning
confidence: 99%
“…Equally important to host defense is a classical pattern of macrophage activation that aids in the elimination of cryptococcal cells (36)(37)(38). In contrast, susceptibility to progressive cryptococcal disease is characterized by a Th2 pattern of cytokine expression, lung eosinophilia, goblet cell metaplasia, and alternative macrophage activation (39)(40)(41).…”
mentioning
confidence: 99%